The Effect of Principal Academic Supervision and Teacher Teaching Performance on Student Achievement at Public Elementary Schools in East Ratahan - Tini Mogea (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2022)
This study aims to describe analyzing and knowing the effect of academic supervision, the effect of teacher performance on achievement, and the simultaneous influence between academic supervision and teacher performance. This research was conducted in an ex-post facto and explanatory research with a quantitative approach. The results showed that the principal's academic supervision contributed positively to student achievement in public elementary schools in East Ratahan. This research has a positive contribution to the development of student learning outcomes and achievement where academic supervision must be implemented to supervise teacher professionals in implementing learning to students. Teacher performance does not significantly contribute to student achievement in public elementary schools in East Ratahan. The implication of this research in learning activities in schools lies in optimizing students' cognitive and learning skills through stimulation and teacher professionalism. Another thing is the nutritional and emotional factors that must be optimized and developed by parents in facilitating their children to learn. The principal's academic supervision and teacher performance simultaneously contribute positively and significantly to student achievement in public elementary schools in East Ratahan. The results of this study have a positive contribution to the learning process which includes curriculum, professionalism, and school managerial systems. Improvements to the curriculum, teacher professionalism, and principal managerial systems must be a holistic entity in its implementation.